UMP and KYTS signed an agreement for a collaboration in German’s engineering programme - UMP, PNC (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) and Sabah Foundation Technical College (KTYS) signed a Memorandum of Agreement (MoA) on academic collaboration for foundations programme involving three engineering courses on August 11, 2016 at Putrajaya.